The Effects of a Blend of Essential Oils in the Milk of Suckling Calves on Performance, Immune and Antioxidant Systems, and Intestinal Microbiota - Luisa Nora; Charles Marcon; Guilherme Luiz Deolindo; Mateus Henrique Signor; Ana Luiza Muniz; Miklos Maximiliano Bajay; Priscila Marquezan Copetti; Bianca Fagan Bissacotti; Vera M. Morsch; Aleksandro Schafer da Silva (Animals)
The objective of the present study was to determine whether the addition of a blend based on the essential oils of cinnamon, oregano, and eucalyptus to the liquid diets of calves would stimulate the immune system combined with anti-inflammatory action, minimize oxidative responses, and alter the intestinal microbiota, consequently enhancing animal growth. Twenty-four male Holstein calves (approximately five days old) were suckled for 60 days, underwent a weaning process, and were followed up until day 75 of the experiment. The calves were divided into control (n = 12) and phytobiotic (n = 12) groups, receiving commercial milk replacer and pelleted concentrate ad libitum. For the phytobiotic group, we added the blend to the liquid diet twice daily at 5 mL/feeding in the first 15 days and 10 mL/feeding until day 60. We detected no differences in weight gain, but animals in the phytobiotic group tended to consume less feed. Calves treated with phytobiotics showed better conversion and feed efficiency than the animals in the control group. Lower leukocyte and lymphocyte counts were observed, as was a higher cholesterol concentration. Immunoglobulin A, ceruloplasmin, and transferrin also differed between groups, with higher IgA and lower levels of acute-phase proteins (ceruloplasmin and transferrin) in calves that consumed the phytobiotic. Higher glutathione S-transferase activity was found in the serum of calves in the treatment group. The intestinal microbiota did not differ between the groups; however, the genera Acinetobacter, Pseudomonas, and Psychrobacter were the most abundant regardless of treatment. We concluded that the blend of oils based on cinnamon, oregano, and eucalyptus improved the calves’ immune and antioxidant systems, improving feed efficiency without affecting the intestinal microbiota.